Subtotal removal of the stratum corneum by brushing as a decontamination strategy after hydrofluoric-acid exposure of human skin - Mini Vijayan, Suvarna; Göen, Thomas; Kaifie-Pechmann, Andrea; Kiesewetter, Franklin; Horch, Raymund E.; Müller-Seubert, Wibke; Drexler, Hans; Kilo, Sonja; Wolfschmidt, Anna (Toxicology Letters, 2026)
Accidents with hydrofluoric acid (HF) can cause systemic poisoning by transdermal penetration of fluoride ions. Abrasive techniques, like mechanical brushing, are occasionally used as a method of decontamination, but their efficacy in reducing systemic fluoride absorption remains unclear. In a modified Franz diffusion-cell model, human skin samples (0.9 mm thickness, n = 6 per group) were exposed to 30 % HF. After one minute of exposure, the supernatant fluid was removed with cotton swabs. With the exception of untreated controls, the skin was then decontaminated either with a water jet alone or combined with brushing, using an electric toothbrush. Samples were collected from the receptor solution at different timepoints during the 72 h post-exposure timeframe. Both strategies were effective when compared to a lack of decontamination. There was no significant difference in cumulative fluoride absorption between the combination of water jet plus brushing and the water jet alone. However, approximately 4–48 h after exposure, the fluoride flux (absorption per hour) was lower in the skin samples treated with the combination of water jet and brushing. This difference was significant at 12 h and 24 h post-exposure. Overall, our results suggest an additional efficacy of mechanical decontamination during the prolonged follow-up period after hydrofluoric-acid exposure. This might be especially relevant in exposure scenarios with a larger skin depot of fluoride, like exposure to higher HF-concentrations. However, future research is needed to place these findings on a broader data basis and to evaluate the safety and efficacy of mechanical decontamination in practice.
CRIS-Team Scopus Importer:2025-12-12
Keywords: Abrasive measures; Brushing; Decontamination; Franz diffusion cell; Human skin; Hydrofluoric acid; Percutaneous absorption